2019
DOI: 10.1111/cfs.12690
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of mentoring to the life skills of youth leaving care in Israel

Abstract: The goal of this study was to examine the contribution of natural mentoring to the improvement of life skills among youth in care in core areas of education, employment, and avoidance of risk behaviours while controlling for personal characteristics and placement history. The sample includes 174 adolescents in residential care in Israel. Results showed that mentoring duration and mentoring functions including mentor as “role model,” “parental figure,” and “independence promoter” significantly contributed to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 33 publications
0
2
0
2
Order By: Relevance
“…Dar mayor prioridad en la preparación de estos jóvenes en su trayectoria de protección a la configuración de un tejido social de apoyo, en el que estén incluidos adultos y coetáneos de entornos inclusivos, trabajando a través del desarrollo de competencias socioafectivas (Ball et al, 2021;Campos et al, 2020;Diaz-Esterri, Goig-Martínez et al, 2021;De-Juanas et al, 2022;Oterholm y Paulsen, 2018); reafirmar estructuras de valores más comunitarias e interdependientes (Moodley et al, 2020); facilitar la accesibilidad de estos jóvenes a las actividades de ocio inclusivo que oferte la comunidad ; afianzar figuras como las del tutor educativo o mentor (Sulimani-Aidan et al, 2019); y reforzar la figura de los profesionales, facilitando la estabilidad de los equipos educativos en los acogimientos residenciales (Martín et al, 2020), son otras de las propuestas y actuaciones de éxito que se consideran necesarias para prevenir que estos jóvenes vulnerables crucen el umbral de la exclusión social una vez alcanzan la mayoría de edad (Morese et al, 2019).…”
Section: Discussionunclassified
“…Dar mayor prioridad en la preparación de estos jóvenes en su trayectoria de protección a la configuración de un tejido social de apoyo, en el que estén incluidos adultos y coetáneos de entornos inclusivos, trabajando a través del desarrollo de competencias socioafectivas (Ball et al, 2021;Campos et al, 2020;Diaz-Esterri, Goig-Martínez et al, 2021;De-Juanas et al, 2022;Oterholm y Paulsen, 2018); reafirmar estructuras de valores más comunitarias e interdependientes (Moodley et al, 2020); facilitar la accesibilidad de estos jóvenes a las actividades de ocio inclusivo que oferte la comunidad ; afianzar figuras como las del tutor educativo o mentor (Sulimani-Aidan et al, 2019); y reforzar la figura de los profesionales, facilitando la estabilidad de los equipos educativos en los acogimientos residenciales (Martín et al, 2020), son otras de las propuestas y actuaciones de éxito que se consideran necesarias para prevenir que estos jóvenes vulnerables crucen el umbral de la exclusión social una vez alcanzan la mayoría de edad (Morese et al, 2019).…”
Section: Discussionunclassified
“…U ovom se istraživanju potvrdilo da mentori primjenjuju nekoliko različitih uloga u svom radu -od druženja s njima, istinske podrške, bivanja uzorom mladima, kao i u istraživanjima Sulimani Aidana (2018) i Rhodesa (2005). Prema teorijama mentoriranja, proces stvaranja pozitivnih promjena u životu mladih uključuje mentore koji služe različitim funkcijama u odnosu (Ahrens i sur., 2008;Greeson i sur., 2010;Greeson i Bowen, 2008;Sulimani-Aidan, 2016a, 2016bSulimani-Aidan, Melkman i Greeson, 2019). Stoga mentorstvo valja percipirati kao holističke odnose koji uključuju niz različitih dimenzija (Sulimani-Aidan i sur., 2019).…”
Section: Diskusijaunclassified
“…Youth who are weaned from institutional care and transition from dependence to independence require adequate mentoring to be able to cope resiliently in the wider outside world ( Sulimani-Aidan et al, 2019 , p. 345). A South African study that looked at the resilience of girls leaving a care institution showed that they remained resilient because they readily embraced motherhood (and related responsibilities), faith and an attitude of gratitude for the care they received in the care institution ( Hlungwani and van Breda 2020 , p. 918).…”
Section: Introductionmentioning
confidence: 99%